Design Thinking in Pharmacy Education: The Future of Classroom Preparation. (26th June 2020) - Slater, Nicole A.; Dhanasekaran, Muralikrishnan; Govindarajulu, Manoj
Abstract: Design thinking is on the rise as a novel method for creative problem solving in healthcare professional programs. This article will focus on implementation of the concepts of design thinking in the classroom, its utility in pharmacy education, and the advantages it provides from both the faculty and students' perspectives within the practice‐ready pharmacy curriculum.